2016
DOI: 10.1007/978-981-10-0448-3_46
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic-Based Gait Phase Detection Using Passive Markers

Abstract: With the advancement in technology, gait analysis plays a vital role in sports, science, rehabilitation, geriatric care, and medical diagnostics. Identification of accurate gait phase is of paramount importance. The objective of this paper is to put forward a novel approach via passive marker-based optical approach that automatically recognizes gait subphases using fuzzy logic approach from hip and knee angle parameters extracted at RAMAN lab at MNIT, Jaipur. In addition to stance phase and swing phase, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Analytical study of human walk and gait cycle started with Galileo, Da Vinci, and Newton's description in the fifteenth and sixteenth Centuries. Weber brothers in 1836 Germany gave the earliest apt description of the gait cycle [17]. In recent years, clinical analysis of human gait has gained traction, with the seminal work done by Perry et al [20], and Whittle [2].…”
Section: Human Gaitmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical study of human walk and gait cycle started with Galileo, Da Vinci, and Newton's description in the fifteenth and sixteenth Centuries. Weber brothers in 1836 Germany gave the earliest apt description of the gait cycle [17]. In recent years, clinical analysis of human gait has gained traction, with the seminal work done by Perry et al [20], and Whittle [2].…”
Section: Human Gaitmentioning
confidence: 99%
“…According to Perry's Classical gait model [20], the average contribution of sub-phases of a gait cycle as a whole on a time scale is mentioned in Table 1. However, a few authors have reported loading response as 0-10% by considering 7 sub-phases in a gait cycle [17,21].…”
Section: Human Gaitmentioning
confidence: 99%
See 1 more Smart Citation
“…C. Prakash et al described a unique method for identifying gait phases by utilizing an optical approach with passive markers. It uses fuzzy logic to automatically recognize different subphases of gait, resulting in a precise and reliable measurement useful for analyzing gait abnormalities in patients and for the use in the development of control strategies for active lower-extremity prosthetics and orthotics [9]. Taborri et al proposed a distributed classifier for gait phase detection in an active knee orthosis for pediatric subjects with neurological diseases.…”
Section: Introductionmentioning
confidence: 99%